Different diets with and without inclusion of antimicrobial additives alter the toxicity of swine manure to springtails and earthworms - Suélen Serafini; Kaine Cristine Cubas da Silva; Junior Gonçalves Soares; Ana Paula Maccari; Julia Corá Segat; Aleksandro Schafer da Silva; Diovani Paiano; Dilmar Baretta (Bioscience Journal, 2020)
The objective of this study was to measure the impact on part of soil fauna of application of non-stabilized (fresh) manure from post-weaning pigs fed diets formulated with or without dual-purpose wheat, and with or without the use of antimicrobial growth-promoting additives (100 mg kg-1 doxycycline + 50 mg kg-1 colistin + 250 mg kg-1 Zn oxide). Two species of edaphic organisms were evaluated, the springtails Folsomia candida and the earthworms Eisenia andrei, using ecotoxicological avoidance behavior tests. The treatments were swine manure from: RR: Reference Ration; WR: Wheat Reference; RA: Reference Ration + Antimicrobial Additives; WA: Wheat Reference + Antimicrobial Additives). The doses of waste used for treatments were as follows: 0, 5, 10, 20, 30, 40, 65 and 100 m³ ha-1 for the springtails and 0, 5, 10, 20, 30, 40 and 65 m³ ha-1 for the earthworms, applied in the Oxisol. The experimental design was completely randomized with five replicates. The use of non-stabilized swine manure did not affect the avoidance behavior of F. candida at any dose, regardless of the use of antimicrobial or wheat additives. For E. andrei, there was avoidance behavior at all treatments and doses used. These avoidance behaviors were related to the sensitivity of each species of soil organism. The avoidance behavior for earthworms was related to the doses of non-stabilized swine manure in soil and not to the various diets and/or the use of growth-promoting additives.